Fabrication and quality factor control of a microelectromechanical system resonator with linear differential drive - Anthony, C; Turnbull, R; Wei, X; Ward, M; Collins, S (2010)
The fabrication, characterisation and quality factor control of a microelectromechanical system resonator with differential drive and readout is reported. The differential drive results in a linear relationship between the AC drive voltage and the applied force. Furthermore, the static DC force and the undesirable force at the second harmonic frequency (introduced by other driving methods) are also reduced. Differential readout is employed in order to minimise undesirable common-mode signals in the detection electronics. The device has been fabricated in silicon on insulator (using the Integram high aspect ratio micromachining process at QinetiQ) and fully characterised. The ability to track the resonant frequency with fine resolution is related to the quality factor of the resonant system. Commonly used detection techniques such as slope detection and phase detection both require a high quality factor, however, resistance to motion caused by air damping results in a low quality factor - degrading the performance of the sensor. The low-pressure quality factor is measured as being >5500 and reduces to ∼10 at atmospheric pressure. The linear relationship between AC drive voltage and resultant force is exploited in conjunction with an electronic readout architecture yielding the device velocity to implement a force feedback technique - increasing the quality factor of the resonator. © 2010 © The Institution of Engineering and Technology.